The Organization Ecology of Interest Communities
XIII, 285 p.
Keywords: This volume summarizes the origins and development of the organization ecology approach to the study of interest representation and lobbying, and outlines an agenda for future research. Multiple authors from different countries and from different perspectives contribute their analysis of this research program.